Distribution characteristics of phosphoric acid and PTFE binder on Pt/C surfaces in high-temperature polymer electrolyte membrane fuel cells: Molecular dynamics simulation approach - Kwon, Sung Hyun; Lee, So Young; Kim, Hyoung-Juhn; Jang, Seung Soon; Lee, Seung Geol (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
To analyze the effects of binder content on the performance and durability of high-temperature PEMFC, we investigate detailed distribution of PTFE-binder whose content ranges from 7.7 to 35.1 wt% on Pt/C models in the presence of H3PO4 at room (298.15 K) and operating (433.15 K) temperatures. Pair correlation function (PCF) analysis shows that the distribution of H3PO4 on the Pt particle significantly changes as a function of PTFE-binder content beyond 20.0 wt% at 298.15 K due to the onset of Pt particle coverage by PTFE-binder starts. However, under 433.15 K, the higher kinetic energy enables more H3PO4 to access the Pt surface to maintain greater contact. In case of H3PO4 on the carbon surface, the intensities of PCF significantly decrease with increasing PTFE-binder levels up to 20.0 wt% at both 298.15 and 433.15 K as the carbon surface becomes occupied by the PTFE-binder up to similar to 20.0 wt%. The surface coverage analysis also shows that the H3PO4 coverage on Pt surface decreases from 72.4 to 30.5% with increasing PTFE-binder content from 7.7 to 35.1 wt% at 298.15 K. However, the H3PO4 coverage on Pt surface is significantly higher at 433.15 K in comparison to that at 298.15 K because H3PO4 could still permeate the PTFE-binder to contact the Pt particle due to the favorable interactions. (C) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.